Pengaruh Kualitas Produk, Desain Produk, Green Product dan Brand Image terhadap Keputusan Pembelian Produk Kerajinan Gerabah Kasongan: - Rizky Andrian; Agus Dwi Cahya; Muinah Fadhilah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of Product Quality, Product Design, Green Product, Brand Image, and Purchase Decision variables. The results of the research on the t test indicate that the Product Quality variable (X1) has no significant effect on purchasing decisions with a significance value of 0.432 > 0.05 and a t count value 1.98498 < t table 4.020; Product Design variable (X2) has no significant effect on purchasing decisions with a significance value of 0.931 > 0.05 and a t-count value of 1.98498 < t table 4.020; Green Product variable (X3) has no significant effect on purchasing decisions with a significance value of 0.270 > 0.05 and a t-count value of 1.98498 < t table 4.020; Brand Image variable (X4) has no significant effect on purchasing decisions with a significance value of 0.451 > 0.05 and a t-count value of 1.98498 < t table 4.020. Based on the results of the F test, the variables of product quality, product design, Green Products and Brand Image simultaneously do not have a positive effect on the purchasing decision variables, because the significance value is 0.681 > 0.05. Keywords : Product Quality, Product Design, Green Product, Brand Image, Purchase Decision